The Use of Museums as a Learning Resource in the Museology Course at the Islamic University of North Sumatra - Muhammad Ricky Hardiyansyah; Pulung Sumantri; Surya Aymanda Nababan; Aditya Darma; Aizza Nabila (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to analyze the use of museums as a source of learning in the Museology course at the Islamic University of North Sumatra (UISU). With a descriptive qualitative approach, this study collects data through interviews, observations, and documentation studies. The focus of the research lies in how museums are used to support theoretical and practical learning, the role of lecturers as facilitators, and students' perceptions of museum-based learning experiences. The results of the study show that the museum is used as a learning laboratory with activities such as educational visits, curatorial analysis, and collection cataloging practices. This learning allows students to relate theory to real-life experience, which enhances their understanding of museum management concepts. Lecturers play an active role as planners, discussion facilitators, and liaisons between universities and museums. Meanwhile, students stated that museum-based learning provides an exciting, in-depth experience and strengthens practical skills. However, this study also found several challenges, such as limited access, inadequate museum facilities, and suboptimal coordination between the campus and the museum. This study recommends increasing cooperation between universities and museums, improving museum facilities, and integrating digital technology to support distance learning. Museums have proven to play a strategic role not only as a place for cultural preservation, but also as a learning resource that supports the development of students' academic and professional competencies. In conclusion, the use of museums in Museology courses has a significant positive impact, although it requires continuous innovation and support to overcome existing challenges.